Approaching biblical archaeology - Frendo, Anthony J. 1950-; Bloomsbury T&T Clark (London, England Zed Books, 2021)
"A concise introduction to biblical archaeology, covering the bible in its ancient context and broader cultural milieu and introducing the discipline of archaeology to biblicists"
Acknowledgements -- Preface -- 1. Introduction -- 2. What did the Excavators Actually Find? The Archaeological Data and their Interpretation -- 3. Artefacts: Inscribed and Uninscribed -- 4. Earlier, Concurrent, or Later? Stratigraphy as the Backbone of Archaeology -- 5. Adducing the Evidence: Without Going Round in Circles -- 6. In Practice: A Two-Way Flow of Traffic - Archaeology - Bible -- 7. Conclusions -- Bibliography -- Index of References -- Index of Authors
Includes bibliographical references and index
Also published in print
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Bible -- Antiquities; Archaeology; Archaeology and history; Biblical exegesis & hermeneutics; Electronic books